2018
DOI: 10.1186/s12944-018-0815-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral selenium and magnesium co-supplementation on lipid metabolism, antioxidative status, histopathological lesions, and related gene expression in rats fed a high-fat diet

Abstract: BackgroundSupplementation with Selenium (Se) has been shown to lower blood cholesterol and increase tissue concentrations of the antioxidant glutathione (GSH); however, the effects of Se supplementation, in combination with supplemental magnesium, on high fat-induced hyperlipidemia have not been studied. This study was designed to elucidate the effects of oral selenium and magnesium co-supplementation on antihyperlipidemic and hepatoprotective, antioxidative activities, and related gene expression in a hyperli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 26 publications
5
36
0
1
Order By: Relevance
“…A recent study by Castillo-Quan et al [38] reported that Li is an inhibitor of glycogen synthase kinase 3 (GSK-3), an enzyme that regulates glycogen levels in tissues and can reduce triglyceride concentrations in flies, even when they feed on high-carbohydrate diets, which would favor a lower accumulation of fat mass in runners due to the greater use of fat as an energy substrate in the training sessions. In addition, several studies have reported that, at low doses, Li protects cells against death caused by OS [38,39], and it has been reported that OS favors the deposition and accumulation of fat mass [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Castillo-Quan et al [38] reported that Li is an inhibitor of glycogen synthase kinase 3 (GSK-3), an enzyme that regulates glycogen levels in tissues and can reduce triglyceride concentrations in flies, even when they feed on high-carbohydrate diets, which would favor a lower accumulation of fat mass in runners due to the greater use of fat as an energy substrate in the training sessions. In addition, several studies have reported that, at low doses, Li protects cells against death caused by OS [38,39], and it has been reported that OS favors the deposition and accumulation of fat mass [17].…”
Section: Discussionmentioning
confidence: 99%
“…TE analyses were performed using inductively coupled plasma mass spectrometry (ICP-MS) following Maynar et al [17].…”
Section: Sample Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other dietary forms of selenium, such as selenomethionine and selenocysteine, are also effectively incorporated into selenoproteins. Several reports suggest the favorable effect of selenium supplements, such as selenomethionine and sodium selenite, on hepatic dysfunction and hepatic steatosis [ 35 , 36 ]. Significant increases in the activity or mRNA levels of selenoproteins, such as Gpx and Txnrd , were found in these reports.…”
Section: Discussionmentioning
confidence: 99%
“…3-Selenium, was purchased from Inter Pharma UK Co., in the form of film coated tablets (Selenium-ACE). The drug was ingested via gastric intubation once daily in a dose of 0.05mg/kg body weight for 4 weeks [21] .…”
mentioning
confidence: 99%